2010
DOI: 10.1136/ard.2010.129171
|View full text |Cite
|
Sign up to set email alerts
|

The interferon regulatory factor 5 gene confers susceptibility to rheumatoid arthritis and influences its erosive phenotype

Abstract: This study provides the 'association and linkage proof' establishing IRF5 as a RA susceptibility gene and the identification of a genetic factor that seems to contribute to the modulation of the erosive phenotype. Further studies are warranted to clarify the role of IRF5 in RA and its subphenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 28 publications
1
43
0
1
Order By: Relevance
“…In a Spanish RA case-control study, the 5' SNP rs2004640, rs752637, and rs10954213 and the SNP rs10488631 were found to have stronger associations with ACPA-negative RA 10 . A study with French and Western European RA family trios reported the risk effects of the 3 SNP rs3757385, rs2004640, and rs10954213, where the signals were also stronger in the RF-negative RA subgroup 11 . Meanwhile, contradictory results were observed from a Euro-American and a Korean RA case-control study.…”
Section: Discussionmentioning
confidence: 99%
“…In a Spanish RA case-control study, the 5' SNP rs2004640, rs752637, and rs10954213 and the SNP rs10488631 were found to have stronger associations with ACPA-negative RA 10 . A study with French and Western European RA family trios reported the risk effects of the 3 SNP rs3757385, rs2004640, and rs10954213, where the signals were also stronger in the RF-negative RA subgroup 11 . Meanwhile, contradictory results were observed from a Euro-American and a Korean RA case-control study.…”
Section: Discussionmentioning
confidence: 99%
“…IRF5 confers susceptibility to RA and was able to influence its erosive phenotype in European Caucasians [135]. Moreover this correlation was furtherly confirmed in a Korean [136], Tunisian [137] and Japanese [138] populations.…”
Section: Rheumatoid Arthritismentioning
confidence: 86%
“…[83]); RA [67]; RA in European Caucasian [135], Korean [136], Tunisian [137] and Japanese populations [138];…”
Section: Tlr10mentioning
confidence: 99%
“…Indeed, an increased expression of type I IFN genes by peripheral blood mononuclear cells, also referred to as an IFN signature, has been detected in multiple autoimmune diseases. IRF5 gene encodes a member of the IRF family, a group of transcription factors with diverse roles, including virus-mediated activation of interferon, and modulation of cell growth, differentiation, apoptosis, and immune system activity [106].…”
Section: Irf5-interferon Regulatory Factormentioning
confidence: 99%